2022
DOI: 10.1021/acs.jpcc.1c10377
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aspect Ratio in the Photoluminescence of Single CdSe/CdS Dot-in-Rods

Abstract: The elongated shape of CdS nanorods enables linearly polarized photoluminescence (PL) emission from the core/shell CdSe/CdS dot-in-rod (DR) nanocrystals. This work unravels the role of aspect ratios of CdS nanorods in the PL emission of single CdSe/CdS DRs using single-dot PL spectroscopy. We find that as the aspect ratio increases, the PL quantum yield and lifetime significantly reduce, but the PL blinking is suppressed, and the effect on the PL spectrum is less. The correlation between the degree of polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…The normalized on-and off-time probability densities [45][46][47] are the fingerprint of QD blinking studies to investigate and compare the blinking activities of single QDs on silicon and monolayer MoS 2 . According to the two peaks of PL intensity histograms in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The normalized on-and off-time probability densities [45][46][47] are the fingerprint of QD blinking studies to investigate and compare the blinking activities of single QDs on silicon and monolayer MoS 2 . According to the two peaks of PL intensity histograms in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The splitting is comparable to thermal energy at room temperature, resulting in a thermal population of holes across all four bands . However, uniaxial strain along the c -axis is known to energetically red-shift light hole states more significantly than heavy hole states, and the light hole state becomes the ground state of CdSe NC cores in core/shell NRs. ,,, If the anisotropic strain is strong enough, the splitting of the band-edge states can become larger than the thermal energy, lifting the state degeneracy.…”
Section: Resultsmentioning
confidence: 99%
“…3 CdSe/CdS dot-in-rod structures have been widely investigated. 8,13,15,17,20,21 A CdSe core embedded in a prolate or rod-shaped CdS shell contracts along the c-axis, imposing uniaxial compression on the CdSe core. However, only weak uniaxial strain is typically realized in such structures.…”
mentioning
confidence: 99%
“…In Section we described calculations which show that strain is an important factor generating a NR-like electronic structure in DiRs. This is consistent with polarization measurements where increasing rod lengths increase the system strain,and result in more polarized emission. , Beyond aspect ratio alone, the position of the core within the NR also matters. If the core is positioned all the way at one end, the relatively short rod component in that direction reduces the PL polarization due to a weakly polarized field in that direction …”
Section: Steady State Optical Properties Of Cd-chalcogenide Nrs and N...mentioning
confidence: 99%
“…While trapping-induced type-B blinking has been shown to be dominant in CdSe NRs, , in CdSe NR heterostructures, type-A blinking, which can be due to either charging or trapping, has been reported in addition to type-B blinking. ,, In particular, type-A blinking due to a charging mechanism has been shown in CdSe/CdS DiRs via fluorescence lifetime-intensity distribution (FLID). , Separately, aspect-ratio-dependent CdSe/CdS DiR blinking studies showed reduced type-A blinking for longer NRs, which the authors ascribed to reduced wave function overlap with trap states, suggesting a trapping-induced blinking mechanism. In this case, the core size and shell thickness were kept relatively constant, and only the shell length was increased to tune the aspect ratio.…”
Section: Excited State Relaxation In Semiconductor Nrsmentioning
confidence: 99%